Chiquita the Doll Lady; signed: "Mite" fully yours, Chiquita (1901)
Chiquita the Doll Lady; signed: "Mite" fully yours, Chiquita. The 31-year-old Cuban-born woman was 26 inches tall and weighed 18 pounds.